2019
DOI: 10.24018/ejeng.2019.4.10.1605
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structures of ZnO by Aggregates of Atoms and Interaction of Two Monolayers

Abstract: The first-principles calculations are useful for determining electronic and structural properties for a model that simulates a material composed of atomic clusters of ZnO through the analysis of interaction energies and charge distribution. The two-dimensional structural form of ZnO aggregates shows regularly flat hexagons obtained in models of 6, 27 and 54 atoms of Zinc and Oxygen. The structure of a three-dimensional system was determined by dynamics calculations by using the interaction of a pair of monolay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The development of the family of M06 hybrid functionals is important for a range of applications in materials science [24], based on the results of calculations of ZnO structures and structural analysis, it is applied to different methodologies where it is observed that it produces high accuracy. The way to know the correspondence of a three-dimensional structure is done by means of geometry optimization calculations to determine the minimum energy structure [25]. The structural nature of the particles is represented by aggregates that form systems of atomic layers of minimum energy, and some studies show different types with a hexagonal structural shape, giving a more detailed perspective of the mechanism of bond formation for atomic systems.…”
Section: Methodsmentioning
confidence: 99%
“…The development of the family of M06 hybrid functionals is important for a range of applications in materials science [24], based on the results of calculations of ZnO structures and structural analysis, it is applied to different methodologies where it is observed that it produces high accuracy. The way to know the correspondence of a three-dimensional structure is done by means of geometry optimization calculations to determine the minimum energy structure [25]. The structural nature of the particles is represented by aggregates that form systems of atomic layers of minimum energy, and some studies show different types with a hexagonal structural shape, giving a more detailed perspective of the mechanism of bond formation for atomic systems.…”
Section: Methodsmentioning
confidence: 99%